2023
DOI: 10.1039/d3fo01443f
|View full text |Cite
|
Sign up to set email alerts
|

Association of pre-diagnosis specific color groups of fruit and vegetable intake with ovarian cancer survival: results from the ovarian cancer follow-up study (OOPS)

Yu-Yang Liu,
Ting-Ting Gong,
Yi-Zi Li
et al.

Abstract: Pre-diagnosis fruit and vegetable intake from various color groups, especially the green and red/purple ones, may improve OC survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(112 reference statements)
1
0
0
Order By: Relevance
“…For example, Liu et al showed that green and red/purple FV were associated with improved ovarian cancer survival, whereas no association was found for orange/yellow and white FV. 45 Similarly, our study found that green, white and red/purple FV were associated with lower CVD and cancer mortality, whereas no such association was found for orange/yellow FV. 46 Grouping the FV by colors thus provided additional information for understanding the associations of dietary patterns with different diseases.…”
Section: Discussionsupporting
confidence: 54%
“…For example, Liu et al showed that green and red/purple FV were associated with improved ovarian cancer survival, whereas no association was found for orange/yellow and white FV. 45 Similarly, our study found that green, white and red/purple FV were associated with lower CVD and cancer mortality, whereas no such association was found for orange/yellow FV. 46 Grouping the FV by colors thus provided additional information for understanding the associations of dietary patterns with different diseases.…”
Section: Discussionsupporting
confidence: 54%